Referendum Patterns In General Regional Challenges of Regional Head In 2015 In Three Districts; Tasikmalaya, Blitar And North Timor - Abu Tamrin; Nur Rohim Yunus (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2017)
The phenomenon of a single candidate for regional heads occurred in the general elections of regionalheads in 2015, especially in three districts of Tasikmalaya, Blitar and North Central Timor. Thesethree areas have varying reasons for the occurrence of only one candidate pairs in the election. Inreality this condition is a form of empirical democracy that can not be rejected and avoided. So thenattempted to find a solution to the democratic party with the condition of only one candidate pair canstill run well. Therefore, the Constitutional Court decided to continue to provide an opportunity forthe regions to conduct regional head elections with only one candidate pair, using mechanisms ofagreeing and disagreeing, or so-called referendum patterns or polls. The public is only obliged todecide whether to agree or disagree with the candidate for the regional head who follows the generalelection. DOI: 10.15408/jch.v5i2.7092